2020
DOI: 10.1002/adom.202000858
|View full text |Cite
|
Sign up to set email alerts
|

Color‐Tunable Circularly Polarized Luminescence with Helical Polyacetylenes as Fluorescence Converters

Abstract: parameter for judging the material performance, [30] in which the maximum |g lum | value is 2 when absolutely left-handed or right-handed CPL emission is generated. Nevertheless, the |g lum | values of most reported CPL-active materials are mainly located between 10 −5 and 10 −2 , which are far from our expectation and cannot satisfy the demands for future applications. On the other hand, it is well-acknowledged that multicolor emissions especially RGB colors are important in display technology. Therefore, in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
40
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 43 publications
(42 citation statements)
references
References 75 publications
(88 reference statements)
2
40
0
Order By: Relevance
“…[ [164][165][166] and Ma et al [167] have further demonstrated the "Matching Rule" is potentially applicable to numerous chiral matters and achiral fluorophores, clearly confirming the wide universality and superiority of the strategy. Although striking advancements have been and are being achieved continuously, the development of polymer-based CPL materials is still at the infant state.…”
Section: Constructing Cpl-active Polymers Via Physically Blendingmentioning
confidence: 91%
“…[ [164][165][166] and Ma et al [167] have further demonstrated the "Matching Rule" is potentially applicable to numerous chiral matters and achiral fluorophores, clearly confirming the wide universality and superiority of the strategy. Although striking advancements have been and are being achieved continuously, the development of polymer-based CPL materials is still at the infant state.…”
Section: Constructing Cpl-active Polymers Via Physically Blendingmentioning
confidence: 91%
“…To avoid the limitation, emerging advanced materials presenting high performance CPL have been put forward including chiral lanthanide complexes, [10] small organic molecules and chiral polymers. [11][12][13][14] The g lum value in most research is in the range of 10 -3 -10 -1 , which is so far from the practical application. [2] Cholesteric liquid crystals (CLC), as one kind of spontaneous supramolecular self-assembly system, can be obtained upon doping chiral dopants into nematic liquid crystal (LC) host and is often regarded as 1D photonic crystal.…”
Section: Modulation Of Chirality and Intensity Of Circularly Polarized Luminescence Emitting From Cholesteric Liquid Crystals Triggered Bmentioning
confidence: 99%
“…The novel chiral motor MM was judiciously designed with the functional modification of an ethylene glycol spacer on the rotor and synthesis details were shown in Scheme S3 (Supporting Information). The chemical structure of the molecule was comprehensively confirmed by 1 H and 13 C NMR spectroscopies (SI). Our previous studies have proved that the rigid substituent on rotor of the MM resulted in the decrease of the chirality and long half-life time.…”
Section: Synthesis and Characterization Of MMmentioning
confidence: 99%
“…Generally, luminescence dissymmetry factor (g lum = 2(I L -I R )/(I L + I R ), I L and I R are the intensity of the left-and right-handed CPL emissions, respectively) and luminescence quantum yield (QY) are two important parameters to evaluate the level of CPL property. [1,5] So far, sustained efforts have been devoted to new structures and strategies towards CPL-active materials, e.g., chiral luminescent lanthanide and transition-metal complexes, [6] conjugated polymers, [7] small organic molecules, etc., [8] have been exploited. However, one of the greatest challenges on the path toward the practical applications of these CPL-active materials is the dilemma in possessing large g lum and high QY simultaneously.…”
Section: Background and Originality Contentmentioning
confidence: 99%